Safety and Efficacy of Clomiphene Citrate and L-Carnitine in Idiopathic Male Infertility: A Comparative Study - Moradi, Mahmoudreza; Moradi, Asaad; Alemi, Mohsen; Ahmadnia, Hassan; Abdi, Hossein; Ahmadi, Alireza; Bazargan-Hejazi, Shahrzad (Urology Journal, 2010)
PURPOSE: To compare the effects of L-carnitine with clomiphene citrate in idiopathic infertile men. MATERIALS AND METHODS: Fifty-two men with idiopathic infertility were recruited in this randomized controlled trial. They were randomly assigned into 2 treatment groups, group 1 (n = 20) and group 2 (n = 32), who received L-carnitine 25 mg/day and clomiphene citrate 2 gr/day, respectively, for a period of 3 months. RESULTS: Comparing the effect of L-carnitine and clomiphene on sperm parameters before and after the treatment, both medications had influence on sperm count and motility (P = .01). L-carnitine significantly increased the semen volume (P = .001), while clomiphene citrate was significantly associated with the motility percentage and normal morphology (P = .008). CONCLUSION: It seems that the use of clomiphene citrate and L-carnitine, either individually or in combination, as the first step of idiopathic male infertility treatment is reasonable, safe, and effective.